PENGARUH HARGA, KREDIBILITAS, NILAI EMOSIONAL, DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI - Vincentius, Noverino (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study revealed that there are four dimensions that aim to determine the effect of price, credibility, emotional value, and brand awareness on purchasing decisions on Xiaomi smartphone products. Respondents in this study were people who had used Xiaomi smartphones. This research was conducted on 140 respondents using a quantitative approach. Analysis of the data used is multiple linear regression analysis with SPSS statistical software tools. The results of this study indicate that test credibility has no significant effect on Xiaomi smartphone purchase decisions. Price, Emotional Value, and Brand Awareness have a significant effect on Xiaomi's smartphone purchase decisions.